CbrA Is a Stationary-Phase Regulator of Cell Surface Physiology and Legume Symbiosis in Sinorhizobium meliloti - Gibson, Katherine E. (American Society for Microbiology, 2006)
Sinorhizobium meliloti produces an exopolysaccharide called succinoglycan that plays a critical role in promoting symbiosis with its host legume, alfalfa (Medicago sativa). We performed a transposon mutagenesis and screened for mutants with altered succinoglycan production and a defect in symbiosis. In this way, we identified a putative two-component histidine kinase associated with a PAS sensory domain, now designated CbrA (calcofluor-bright regulator A). The cbrA::Tn5 mutation causes overproduction of succinoglycan and results in increased accumulation of low-molecular-weight forms of this exopolysaccharide. Our results suggest the cbrA::Tn5 allele leads to this succinoglycan phenotype through increased expression of exo genes required for succinoglycan biosynthesis and modification. Interestingly, CbrA-dependent regulation of exo and exs genes is observed almost exclusively during stationary-phase growth. The cbrA::Tn5 mutant also has an apparent cell envelope defect, based on increased sensitivity to a number of toxic compounds, including the bile salt deoxycholate and the hydrophobic dye crystal violet. Growth of the cbrA mutant is also slowed under oxidative-stress conditions. The CbrA-regulated genes exsA and exsE encode putative inner membrane ABC transporters with a high degree of similarity to lipid exporters. ExsA is homologous to the Escherichia coli MsbA protein, which is required for lipopolysacharide transport, while ExsE is a member of the eukaryotic family of ABCD/hALD peroxisomal membrane proteins involved in transport of very long-chain fatty acids, which are a unique component of the lipopolysaccharides of alphaproteobacteria. Thus, CbrA could play a role in regulating the lipopolysaccharide or lipoprotein components of the cell envelope.